Expression of the T helper 17-associated cytokines IL-17A and IL-17F in asthma and COPD. - Doe, C; Bafadhel, M; Siddiqui, S; Desai, D; Mistry, V; Rugman, P; McCormick, M; Woods, J; May, R; Sleeman, M; Anderson, I; Brightling, C (2010)
BACKGROUND: Asthma and COPD are characterized by airway dysfunction and inflammation. Neutrophilic airway inflammation is a common feature of COPD and is recognized in asthma, particularly in severe disease. The T helper (Th) 17 cytokines IL-17A and IL-17F have been implicated in the development of neutrophilic airway inflammation, but their expression in asthma and COPD is uncertain. METHODS: We assessed IL-17A and IL-17F expression in the bronchial submucosa from 30 subjects with asthma, 10 ex-smokers with mild to moderate COPD, and 27 nonsmoking and 14 smoking control subjects. Sputum IL-17 concentration was measured in 165 subjects with asthma and 27 with COPD. RESULTS: The median (interquartile range) IL-17A cells/mm² submucosa was increased in mild to moderate asthma (2.1 [2.4]) compared with healthy control subjects (0.4 [2.8]) but not in severe asthma (P = .04). In COPD, IL-17A(+) cells/mm² submucosa were increased (0.5 [3.7]) compared with nonsmoking control subjects (0 [0]) but not compared with smoking control subjects (P = .046). IL-17F(+) cells/mm² submucosa were increased in severe asthma (2.7 [3.6]) and mild to moderate asthma (1.6 [1.0]) compared with healthy controls subjects (0.7 [1.4]) (P = .001) but was not increased in subjects with COPD. IL-17A and IL-17F were not associated with increased neutrophilic inflammation, but IL-17F was correlated with the submucosal eosinophil count (rs = 0.5, P = .005). The sputum IL-17 concentration in COPD was increased compared with asthma (2 [0-7] pg/mL vs 0 [0-2] pg/mL, P < .0001) and was correlated with post-bronchodilator FEV₁% predicted (r = -0.5, P = .008) and FEV(1)/FVC (r = -0.4, P = .04). CONCLUSIONS: Our findings support a potential role for the Th17 cytokines IL-17A and IL-17F in asthma and COPD, but do not demonstrate a relationship with neutrophilic inflammation.